Analisis Pengaruh Likuiditas, Total Aktiva, dan DER Terhadap Profitabilitas dan Nilai Perusahaan - ST Aminah; Abdul Rakhman Laba; Erlina Pakki (Hasanuddin Journal of Business Strategy, 2019)
This study aims to analyze the effect of liquidity, total assets, and Debt to Equity Ratio(DER) on profitability (ROA) and firm value (PER) on telecommunication companies listed on the Indonesia Stock Exchange (BEI). The samples taken are 30 from five different companies listed on the Indonesia Stock Exchange using the annual report from 2012 - 2017. Data is then analyzed using path analysis method with the assistant of SPSS software. Sobel test and classical assumption test were evaluated beforehand. The results of the study found that liquidity had a negative and significant effect on profitability (ROA), while total assets and DER had a positive and significant effect on profitability. Liquidity and total assets have a positive and significant influence on firm value, while DER has a negative effect on firm value. Profitability has a positive and significant effect on firm value. The mediation test results show that liquidity has a direct and indirect effect on firm value mediated by profitability. Total assets have a direct effect on increasing company value, but interestingly total assets through profitability show insignificant score to impact firm value. DER has a direct and negative effect on firm value, while the results of the probability proved that profitability can mediate the influence between DER on firm value.